2017
DOI: 10.5586/aa.1720
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic effects of Cerbera manghas L. leaf extracts on seedling elongation of four monocot and four dicot test species

Abstract: Exploration of allelochemicals with phytotoxic effects is intended to minimize a current dependency on synthetic herbicides in weed management. Several allelochemicals from the tropical tree <em>Cerbera manghas</em> (sea mango) have been reported as termiticides and bactericides. The present study investigated possible phytotoxic effects of <em>C. manghas</em> leaf extracts under laboratory conditions. Four monocots: barnyard grass (<em>Echinochloa crus-galli</em>), foxtail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
5
12
0
Order By: Relevance
“…According to research results, the sensitivity to the extracts depends on the species and also on the concentration of the foliar extract (Bari and Kato-Noguchi, 2017). The seedlings' growth can be stimulated by compounds in low concentration and, on the contrary, can be reduced or inhibited in high concentrations (Kato-Noguchi et al, 2016), a fact observed in this research for the two lettuce cultivars and barnyard grass.…”
Section: Resultssupporting
confidence: 54%
“…According to research results, the sensitivity to the extracts depends on the species and also on the concentration of the foliar extract (Bari and Kato-Noguchi, 2017). The seedlings' growth can be stimulated by compounds in low concentration and, on the contrary, can be reduced or inhibited in high concentrations (Kato-Noguchi et al, 2016), a fact observed in this research for the two lettuce cultivars and barnyard grass.…”
Section: Resultssupporting
confidence: 54%
“…Additionally, at increased the extract concentrations, greater decreases in the growth seedling of test plant species occurred. The concentrationdependent inhibition on tested plants was also found in Rumex maritimus and Cerbera manghas (Bari and Kato-Noguchi, 2017). These results may be due to the variable amount of the potential inhibitory activity depending on the intensity of phytochemicals and may be responsible for the inhibition of the seedling growth of test plants (Travlos and Paspatis, 2008;Gomaa et al, 2014).…”
Section: Extractionmentioning
confidence: 71%
“…and timothy ( Phleum pratense L.) were selected as the monocots. The test plants were chosen for the experiment because of their known seedling development behaviors and their common use as model plants for laboratory bioassays [14,15,16,17,18]. Germination percentages of the seeds were >90% on average.…”
Section: Methodsmentioning
confidence: 99%